Censorship detected in HN (Honduras) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Honduras. Data sourced from OONI.
Censorship Incident ID: HN-2026-0055. Severity: critical. Confidence: 70%